Exploiting gold nanoparticles for diagnosis and cancer treatments. (19th February 2021) - D'Acunto, Mario; Cioni, Patrizia; Gabellieri, Edi; Presciuttini, Gianluca
Abstract: Gold nanoparticles (AuNPs) represent a relatively simple nanosystem to be synthesised and functionalized. AuNPs offer numerous advantages over different nanomaterials, primarily due to highly optimized protocols for their production with sizes in the range 1–150 nm and shapes, spherical, nanorods (AuNRs), nanocages, nanostars or nanoshells (AuNSs), just to name a few. AuNPs possess unique properties both from the optical and chemical point of view. AuNPs can absorb and scatter light with remarkable efficiency. Their outstanding interaction with light is due to the conduction electrons on the metal surface undergoing a collective oscillation when they are excited by light at specific wavelengths. This oscillation, known as a localized surface plasmon resonance, causes the absorption and scattering intensities of AuNPs to be significantly higher than identically sized non-plasmonic nanoparticles. In addition, AuNP absorption and scattering properties can be tuned by controlling the particle size, shape, and the local refractive index near the particle surface. By the chemical side, AuNPs offer the advantage of functionalization with therapeutic agents through covalent and ionic binding, which can be useful for biomedical applications, with particular emphasis on cancer treatments. Functionalized AuNPs exhibit good biocompatibility and controllable distribution patterns when delivered in cells and tissues, which make them particularly fine candidates for the basis of innovative therapies. Currently, major available AuNP-based cancer therapeutic approaches are the photothermal therapy (PTT) or photodynamic therapy (PDT). PTT and PDT rely upon irradiation of surface plasmon resonant AuNPs (previously delivered in cancer cells) by light, in particular, in the near-infrared range. Under irradiation, AuNPs surface electrons are excited and resonate intensely, and fast conversion of light into heat takes place in about 1 ps. The cancer cells are destroyed by the induced hyperthermia, i.e. the condition under which cells are subject to temperature in the range of 41 °C–47 °C for tens of minutes. The review is focused on the description of the optical and thermal properties of AuNPs that underlie their continuous and progressive exploitation for diagnosis and cancer therapy.